2019
DOI: 10.1111/ijcp.13315
|View full text |Cite
|
Sign up to set email alerts
|

Increased PON lactonase activity in morbidly obese patients is associated with impaired lipid profile

Abstract: Aims:The paraoxonase-1 (PON1) enzyme could play an important role in the antioxidant capacity of high-density lipoprotein. However, there are no studies which analyse the evolution of the three activities of PON1 (PON arylesterase, PON paraoxonase and PON lactonase) after Roux-en-Y Gastric Bypass (RYGB) in morbidly obese subjects. We analysed the association of PON concentration and activities with the evolution of morbidly obese subjects who underwent RYGB, and its relationship with biochemical variables and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
4
1
Order By: Relevance
“…Such relationship was absent in patients with arterial hypertension. However, other authors noted correlations between PON1 activity and HDL-C, TG, or BMI in persons with cardiovascular risk factors [27], also with arterial hypertension [10,11,14,28]. In our study the positive correlation between PON1 and CRP was observed, especially in the group with newly diagnosed hypertension.…”
Section: Discussioncontrasting
confidence: 56%
“…Such relationship was absent in patients with arterial hypertension. However, other authors noted correlations between PON1 activity and HDL-C, TG, or BMI in persons with cardiovascular risk factors [27], also with arterial hypertension [10,11,14,28]. In our study the positive correlation between PON1 and CRP was observed, especially in the group with newly diagnosed hypertension.…”
Section: Discussioncontrasting
confidence: 56%
“…Additionally, several studies by Bajnok et al [29][30][31] reported low PARX activity in obese adults. However, other studies found no alterations in ARE, PARX, and LAC in patients with different degrees of obesity [32,33].…”
Section: Discussionmentioning
confidence: 82%
“…Another factor that has been thoroughly studied in association with PON1 lactonase activity is body weight. Three articles reported on the association between body weight and DHC lactonase activity (Alaminos-Castillo et al, 2019 ; Bacchetti et al, 2019 ; Rupérez et al, 2013 ), Ferré et al ( 2013 ) investigated TBBL and Cervellati et al ( 2018 ) focused on TBL. Of these five articles, three of them found a significant correlation between PON1 lactonase activity and obesity (Alaminos-Castillo et al, 2019 ; Bacchetti et al, 2019 ; Ferré et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Alaminos-Castillo et al ( 2019 ) reported that DHC lactonase activity is significantly decreased in obese subjects compared with nonobese controls, and increases after surgery. Bacchetti et al ( 2019 ) grouped cases into two categories, overweight women and obese women, and detected that DHC lactonase activity is significantly decreased in each subsequent category compared with healthy individuals (Bacchetti et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%